The effect of targeting and interceptive timing tasks on the brain waves of elite and educated athletes - Keshvari, F.; Farsi, A.; Abdoli, B.; Bahrami, A. (PLOS ONE, 2025)
The non-sports studies have separated two processing systems using paradigms of the roles of frontal regions in top-down processing, and the roles of parietal areas in bottom-up processing. However, the dynamics of cortical activity of the two processing systems in exercise have been neglected. This study examined the effect of targeting and interceptive timing tasks on brain waves in 20 participants, including 10 elite athletes and 10 educated individuals. Data were extracted using a 32-channel wireless device while performing basketball free throw and pass-catching tasks. The results of the repeated-measures analysis of variance on spectral power density indicated higher cortical activation in the elite group across all frequency bands (delta, theta, alpha, beta, and gamma). Furthermore, the cortical activation in the delta, theta, and alpha bands was higher in the free-throw task than in the pass-catching task. In most of the frontal sites, several central sites and one site in the parietal region had more cortical activity in the free-throw task than pass-catching in the alpha and theta bands. Findings show that elite subjects performed these tasks with optimized neural resource allocation, reduced cognitive load, and more automatically. Furthermore, enhanced cortical activity within frontal regions during free throw execution compared to pass-catching, coupled with the absence of significant parietal activity differences between these tasks, suggests functional interdependence between these neural processing systems specifically within the context of motor performance.